Efeito da distância de cruzamentos sobre o sucesso reprodutivo e estrutura genética populacional em uma espécie de vereda - Santos, Jessyca Santana (2022)
The vereda palm swamps have great relevance as they are directly associated with the upwelling of the water table. Changes in land use, such as the advance of agricultural activities, can change the characteristics of these environments, contributing to rapid degradation. In some cases, plant species shows trategies for reproduction in order to maximize reproductive success in environments such as vereda. Reproductive success can be influenced by pollen flow (modulated by pollinator vagility and spatial distance) and by genetic diversity (genetic distance and factors such as inbreeding depression and allogamy). Genetic studies with Cerrado plants can help to understand and measure the evolutionary factors that act in this biome, such as molecular markers experiments that have been an important tool in the studies genotypic variability and gene flow in natural plant populations . The underlying idea is that the type of pollination and their occurrence in hydromorphic environments of veredas may be associated with different genetic structures. Thus, the pollen flow in Costus spiralis (Jacq.) Roscoe, a typical plant of suchhumid areas, must be assuredby the hummingbirds' ability to fly long distances in linear vereda environments. To assess the effect of distance on reproductive patterns, hand cross pollinations were performed at different distances and reproductive success was analyzed. We used microsatellite markers (SSR)to analyze genetic diversity for Costus spiralis. To do so, we tested the transferability of primers developed for other species of the same genus and selected the effectively amplified and polymorphic ones to evaluate the population structure. In this study, we observed that Costus spiralis is a self-compatible species, which presents greater reproductive success after pollination among plants in a given cluster (less than 60m distant) than between plants further away. This was corroborated by the preliminary data of the second chapter, which indicated a greater genetic variability within clusters. than between them. We conclude that the hummingbird pollinators efficiently transports the genes, so that there were no differences between the selected clusters along the studied Vereda